2019
DOI: 10.3389/fphar.2019.00658
|View full text |Cite
|
Sign up to set email alerts
|

PQM130, a Novel Feruloyl–Donepezil Hybrid Compound, Effectively Ameliorates the Cognitive Impairments and Pathology in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most frequent type of dementia in older people. The complex nature of AD calls for the development of multitarget agents addressing key pathogenic processes. Donepezil, an acetylcholinesterase inhibitor, is a first-line acetylcholinesterase inhibitor used for the treatment of AD. Although several studies have demonstrated the symptomatic efficacy of donepezil treatment in AD patients, the possible effects of donepezil on the AD process are not yet known. In this study, a novel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…[58] F. Morroni et al found A 1-42 injection affected AKT and MAPK. [59] Motivated by these researches, we tested the downstream proteins in insulin signaling in the present study. It turned out that abnormal insulin signaling in the hippocampus was observed in A group, as evidenced by both phosphorylation of AKT and MAPK reduced in A -induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…[58] F. Morroni et al found A 1-42 injection affected AKT and MAPK. [59] Motivated by these researches, we tested the downstream proteins in insulin signaling in the present study. It turned out that abnormal insulin signaling in the hippocampus was observed in A group, as evidenced by both phosphorylation of AKT and MAPK reduced in A -induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro possibility to pass BBB [69] Feruloyl-donepezil hybrid ability to modify the kinetics of Aβ fibril formation…”
Section: In Vitromentioning
confidence: 99%
“…Morroni et al [69] studied a novel feruloyl-donepezil hybrid compound AB78. The researchers prepared this compound and tested it as a multitarget agentfor the treatmentof neurotoxicity induced by the administration of Aβ 1-42 oligomer (AβO) in mice.…”
Section: Curcumin Hybrids For Ad Therapymentioning
confidence: 99%
“…The fundamental role of oxidative stress in neurodegenerative disorders is recognized, and, also in the early stages, it is possible to observe a significant increase of ROS production [55]. When this phenomenon is efficiently reduced, also the cognitive impairment and the inflammatory processes are successfully counteracted [56,57]. Indeed, there is a close relationship among oxidative stress, aging, and inflammation.…”
Section: The Role Of Aging and Oxidative Stress In Chronic Neurodegenmentioning
confidence: 99%